PENGARUH RETURN ON ASSET, LEVERAGE, KUALITAS AUDIT, KOMITE AUDIT, DAN KARAKTER EKSEKUTIF TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2014-2017 - Kartika Krisnawati, 15.05.52.0335; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2019)
Tax Avoidance is the legitimate minimizing of taxes. The purpose of this research is to examine and analyze the influence of return on asset, leverage, audit quality, audit committees, and executives character on corporate tax avoidance. This research was conducted at the companies listed on the Bursa Efek Indonesia in the observation period 2014-2017. Sampling method used was purposive sampling with 256 samples, consist from 64 companies during the observation period of 4 years. Data in this research were analyzed with multiple linear analysis techniques. The result of this research indicate that return on asset has positive effect on tax avoidance, while the other independen variabel (leverage, audit quality, audit committees, and executives character) has no effect on tax avoidance.